Resins-supported Cu catalysts for the Fenton-like oxidation of phenol from water - Fabio D. Battauz; Fernanda Miranda Zoppas; Nicolás A. Sacco; F. Albana Marchesini (Desalination and Water Treatment)
In recent years, there has been a growing interest in removing emerging contaminants from water, with advanced oxidation processes, such as Fenton oxidation using iron, being commonly explored. This study focuses on the synthesis and characterization of Cu-loaded ion-exchange resins as an alternative for phenol oxidation. The potential of anionic ion exchange resins Purolite A400 (R1), A103Plus (R2), A520E (R3), and Puropack PPA300 (R4) as catalyst supports was investigated. After pretreatment and loading with Cu(II) ions, these materials exhibited promising catalytic performance, with R1Cu and R2Cu showing notable activity that surpassed simple adsorption, evidenced by oxidation reactions. FTIR and SEM EDS, XRD characterization highlighted the chemical stability of the catalytic resins, and leaching tests indicated that R1Cu and R2Cu lost less than of their initial Cu loading. Fenton-like oxidation with H₂O₂ was conducted under various conditions optimized using factorial design methodology. The results demonstrated significant phenol degradation, achieving over 95 % conversion in under 2 h without pH control. Temperature had the most significant impact, and weak anionic resins exhibited the highest Cu retention. These findings underscore the potential of Cu-based Fenton-like systems for wastewater treatment, offering insights into catalyst design and optimization for phenol degradation. Future work will focus on assessing the catalysts' viability in continuous-flow reactors and the toxicity of oxidation byproducts.